FEATURES OF ALIEN AND HARMFUL IDEAS IN SOCIAL NETWORKS (Scientific journal of the Fergana State University, 2023)
Today, social sites have come to the fore in the propaganda of ideological factors, having established themselves as the main means of indoctrination of ideology, considering the fact that the main sources of social sites are in the social networks that we are investigating requires more serious attention to this issue. After all, attempts to manipulate peopleʼs minds can often be found regularly on social networks. The establishment of cultural hegemony is becoming an increasingly common management technology, that is, manipulating the human mind, seizing foreign territories into its sphere of influence. Thus, constant vigilance and vigilance against ideological, ideological and informational attacks and risks affecting the stability of the country, the prevention and elimination of which is a requirement of the era today.